2015
DOI: 10.1007/s00280-015-2919-0
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine with/without mitomycin C: results of a randomized phase II trial of second-line therapy in advanced biliary tract adenocarcinoma

Abstract: Since capecitabine yielded a disappointing outcome and the addition of mitomycin C did not improve the results, new therapeutic strategies need to be explored to improve survival in this disease setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In previous studies, the reported response rates were 2-12% for target therapies and 7-10% for salvage cytotoxic chemotherapies 25-28. Recently, Cereda et al reported that capecitabine with or without mitomycin had a response rate of 3% in a randomized phase II study of a second-line therapy in patients with BTC 24. Considering data from other previous studies, the efficacy of XELOX was slightly better or similar.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In previous studies, the reported response rates were 2-12% for target therapies and 7-10% for salvage cytotoxic chemotherapies 25-28. Recently, Cereda et al reported that capecitabine with or without mitomycin had a response rate of 3% in a randomized phase II study of a second-line therapy in patients with BTC 24. Considering data from other previous studies, the efficacy of XELOX was slightly better or similar.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, a tolerable, feasible, and useful second-line treatment is needed for these patients. There have been several studies investigating potential treatments23,24; however, a standard second-line or salvage treatment has not been established for BTCs. This prospective study suggests that capecitabine plus oxaliplatin might be useful as a second-line therapy in BTCs refractory to the standard GP regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Until 2019, there was no recommended regimen in this setting and the type of chemotherapy regimen varied according to the center/national clinical practices. 2,3 Following the presentation of the 10% with capecitabine plus mitomycine C. 16 In Asian countries, three single-arm phase II trials with S-1 monotherapy after progression on L1 chemotherapy suggested that this compound was safe and moderately efficacious in L2. [17][18][19] Retrospective cohorts and meta-analyses reported conflicting results about the efficacy of FP doublets vs monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoropyrimidines such as 5‐fluorouracil, capecitabine and S‐1 are commonly used in clinical practice. Second‐line chemotherapy, including the combination of mitomycin C and capecitabine vs. capecitabine alone, yielded a disappointing outcome, with the addition of mitomycin C failing to show improved results 24 . A randomized phase II study focusing on the efficacy of the second‐line oxaliplatin plus irinotecan (XELIRI) regimen versus that of irinotecan monotherapy demonstrated a clear progression‐free survival (PFS) benefit 25 .…”
Section: Systemic Therapymentioning
confidence: 99%